2015
DOI: 10.1185/03007995.2015.1031732
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of total cost and economic consequences of progression for patients with newly diagnosed multiple myeloma

Abstract: Background: Few studies have addressed the cost patterns of patients with multiple myeloma (MM) before and after first relapse. This US claims analysis evaluated, from a US health plan perspective, patterns of total direct costs of care from treatment initiation to progression for patients with MM treated with novel agents, using time to next therapy (TTNT) as a proxy measure for progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 24 publications
4
34
1
Order By: Relevance
“…Our findings agree with those from Arikian et al, who used US healthcare data to show that, for the first 3 years of treatment, patients who initiated lenalidomide-based treatments had lower mean monthly total costs compared to those who initiated on bortezomib-based treatments [8]. Arikian et al also demonstrated that the cumulative cost of first-line lenalidomide was approximately $120,000 (€109,000) lower than for first-line bortezomib [8].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings agree with those from Arikian et al, who used US healthcare data to show that, for the first 3 years of treatment, patients who initiated lenalidomide-based treatments had lower mean monthly total costs compared to those who initiated on bortezomib-based treatments [8]. Arikian et al also demonstrated that the cumulative cost of first-line lenalidomide was approximately $120,000 (€109,000) lower than for first-line bortezomib [8].…”
Section: Discussionsupporting
confidence: 92%
“…Arikian et al also demonstrated that the cumulative cost of first-line lenalidomide was approximately $120,000 (€109,000) lower than for first-line bortezomib [8]. These findings further support our recommendation that the most beneficial way to use lenalidomide for patients with newly diagnosed multiple myeloma is at first-line thus capitalising on its increased time to progression/OS and cost impact compared to other choices of first-line treatment.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…This method allows for the selection of untreated patients providing an opportunity to select incident cases or those with SMM. Prior work in the MM population using claims data has relied on the selection of a treated population (15, 16). While the strategy of requiring both appropriate ICD-9-CM codes and the disease-specific treatments can better identify true cases, this approach limits the research question to the treated population and excludes patients who either are at an early disease stage who does not yet require treatment or who forgo treatment for personal or medical reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Current challenges for the management of MM, including bortezomib drug treatment, are resistance development to drugs, increased unsustainable cost [9,10], lack of standardization in the therapeutic steps including stem cell transplantation, and morbidity and mortality due to drugs and/or ongoing resistant incurable neoplastic myeloma disease [4,5,11,12,13]. In silico studies are effective for key decision making during clinicopathological battles against the chronic course of MM [3,7,14,15].…”
Section: Introductionmentioning
confidence: 99%